Pengujian Karakteristik Campuran Laston Lapisan Antara Menggunakan Batu Sungai Pucak Kabupaten Maros - Mita Palebangan; Robert Mangontan; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The implementation of road pavement construction so far has used materials imported from other places, and most of the road pavement constructions have been damaged before reaching the design life, so maintenance is carried out and even additional coating is given. This study aims to test the characteristics of the mixture of Laston Lapis Antara by utilizing Sungai Pucak aggregate according to laboratory tests. The research method is the Conventional Marshall test which is used to determine the KAO, then the manufacture of the KAO test object to obtain the Marshall Remaining Stability (SMS). The results showed that the characteristics of the aggregates originating from the Pucak River, Maros Regency for the Laston Lapis Antara mixture were in accordance with the General Specifications of Highways in 2018. The results of the characteristic test of the conventional Marshall mixture obtained that the values of stability, flow, VIM, VMA, and VFB all met the General Bina specifications. Marga in 2018. The Marshall Immersion test has complied with the 2018 General Highways specifications, where the value is 95.56%≥90%.